Meaning in life: a comparative study among individuals with low, moderate and high depressive symptomatology - Κλεφτάρας, Γιώργος; Ψαρρά, Ευαγγελία; Καλαντζή - Αζίζι, Αναστασία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF